1994
DOI: 10.1128/aem.60.1.377-384.1994
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an insertion sequence (IS1051) from Xanthomonas campestris pv. dieffenbachiae with potential use for strain identification and characterization

Abstract: A new insertion sequence was isolated from Xanthomonas campestris pv. dieffenbachiae. Sequence analysis showed that this element is 1,158 bp long and has 15-bp inverted repeat ends containing two mismatches. Comparison of this sequence with sequences in data bases revealed significant homology with Escherichia coli IS5. IS1051, which detected multiple restriction fragment length polymorphisms, was used as a probe to characterize strains from the pathovar dieffenbachiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…rRNA genes have highly conserved sequences, and their potential usefulness in the identification and phylogenetic studies of bacteria has been demonstrated (2,9). Specific sequences from genomic or plasmid DNA, such as repetitive elements and insertion sequences, provided useful probes for the assessment of genetic diversity and also allowed a better understanding of the pathogen population structure (1,4,8,18,28,29). Both ribotyping and RFLP analysis with the use of different DNA probes facilitated the study of the population structure of X campestris pv.…”
mentioning
confidence: 99%
“…rRNA genes have highly conserved sequences, and their potential usefulness in the identification and phylogenetic studies of bacteria has been demonstrated (2,9). Specific sequences from genomic or plasmid DNA, such as repetitive elements and insertion sequences, provided useful probes for the assessment of genetic diversity and also allowed a better understanding of the pathogen population structure (1,4,8,18,28,29). Both ribotyping and RFLP analysis with the use of different DNA probes facilitated the study of the population structure of X campestris pv.…”
mentioning
confidence: 99%
“…Xanthomonas axonopodis pv. dieffenbachiae is the aetiological agent of bacterial blight of aroids (BBA), first described in the USA on Dieffenbachia maculata in 1939 aroid species is related to geographic origin and host plant (Chase et al, 1992;Berthier et al, 1994;Khoodoo & Jaufeerally-Fakim, 2004). Two phylogenetically distinct groups of strains pathogenic to aroids have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of DNA probes have been used for RFLP analysis of bacterial species. Avirulence (avr) genes (1,18), hrp genes (4,13,33,36), and repetitive sequences that either are of unknown nature (7,8,10,13) or are transposable elements (1,3,12,18) have been useful for studies on the population structure within pathovars, for comparing different pathovars, and for differentiating nonpathogenic and pathogenic Xanthomonas strains. Depending on the probe used, variability was observed at different levels.…”
mentioning
confidence: 99%